Leadership-Based Quality Assurance Management in Islamic Educational Institutions - Nur Efendi (JMPI: Jurnal Manajemen, Pendidikan dan Pemikiran Islam, 2024)
This study investigates leadership-based quality assurance management in an Islamic educational institution, focusing on MAN 3 Tulungagung. The study aims to examine how leadership shapes quality assurance practices, influences institutional quality outcomes, and interacts with quality management processes. A qualitative case study design was employed to explore leadership practices and organizational dynamics within their natural context. Data were collected through semi-structured interviews, observations of institutional activities, and document analysis, followed by thematic analysis to identify patterns and relationships. The findings reveal that leadership plays a pivotal role in establishing structured quality assurance systems, aligning institutional vision with operational practices, and fostering a culture of accountability and continuous improvement. Leadership practices such as supervision, coordination, and professional support contribute to enhanced teaching quality, improved student engagement, and effective institutional management. The study also demonstrates an interconnected process in which leadership drives implementation, institutional processes sustain performance, and evaluation outcomes inform strategic refinement. These findings highlight the importance of leadership in sustaining effective quality assurance management within Islamic educational institutions.